EFL Learners’ Strategies and Obstacles in Vocabulary Acquisition at the Second Semester TBI STAIN Mandailing Natal - Nurkholijah, Nurkholijah; Damanik, Lia Agustina; Fitriani, Fitriani (MUDABBIR Journal Research and Education Studies, 2025)
Vocabulary is a central aspect of second language learning as it provides the foundation for effective communication. However, acquiring and retaining new vocabulary remains a challenge for many EFL learners. This study aimed to analyze the strategies employed by EFL learners in acquiring vocabulary and to explore the obstacles they encountered in the process. The research was conducted among 25 second-semester students of the English Education Department (Tadris Bahasa Inggris) at STAIN Mandailing Natal. A mixed-method approach was employed, combining quantitative data from questionnaires with qualitative data from semi-structured interviews. The findings revealed that cognitive strategies were the most frequently employed by learners, followed by metacognitive, social, determination, and memory strategies. Meanwhile, the major obstacles faced by learners included limited exposure to English, difficulty in memorizing vocabulary, and low motivation. The study concludes that while learners actively adopt various strategies, their progress is hindered by contextual and psychological challenges. These findings suggest the importance of providing meaningful exposure to English and designing strategy-based instruction to enhance learners’ vocabulary acquisition.